3D morphometric analysis of calcified cartilage properties using micro-computed tomography. Issue 1 (January 2019) - Kauppinen, S.; Karhula, S.S.; Thevenot, J.; Ylitalo, T.; Rieppo, L.; Kestilä, I.; Haapea, M.; Hadjab, I.; Finnilä, M.A.; Quenneville, E.; Garon, M.; Gahunia, H.K.; et al.
Summary: Objective: Our aim is to establish methods for quantifying morphometric properties of calcified cartilage (CC) from micro-computed tomography (μCT). Furthermore, we evaluated the feasibility of these methods in investigating relationships between osteoarthritis (OA), tidemark surface morphology and open subchondral channels (OSCCs). Method: Samples ( n = 15) used in this study were harvested from human lateral tibial plateau ( n = 8). Conventional roughness and parameters assessing local 3-dimensional (3D) surface variations were used to quantify the surface morphology of the CC. Subchondral channel properties (percentage, density, size) were also calculated. As a reference, histological sections were evaluated using Histopathological osteoarthritis grading (OARSI) and thickness of CC and subchondral bone (SCB) was quantified. Results: OARSI grade correlated with a decrease in local 3D variations of the tidemark surface (amount of different surface patterns ( r s = −0.600, P = 0.018), entropy of patterns (EP) ( r s = −0.648, P = 0.018), homogeneity index (HI) ( r s = 0.555, P = 0.032)) and tidemark roughness (TMR) ( r s = −0.579, P = 0.024). Amount of different patterns (ADP) and EP associated with channel area fraction (CAF) ( r p = 0.876, P < 0.0001; r p = 0.665, P = 0.007, respectively) and channel density (CD) ( r p = 0.680, P = 0.011; r p = 0.582, P = 0.023, respectively). TMR was associated with CAF ( r p = 0.926, P < 0.0001) and average channel size ( r p = 0.574, P = 0.025). CC topography differed statistically significantly in early OA vs healthy samples. Conclusion: We introduced a μ-CT image method to quantify 3D CC topography and perforations through CC. CC topography was associated with OARSI grade and OSCC properties; this suggests that the established methods can detect topographical changes in tidemark and CC perforations associated with OA.